2011
DOI: 10.1515/bmc.2011.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of CRF family peptides in the regulation of food intake and anxiety-like behavior

Abstract: Corticotropin-releasing factor (CRF) and the urocortins (UCN1, UCN2, and UCN3) belong to the CRF family of peptides and are the major regulators of the adaptive response to internal and external stresses. The actions of CRF and UCNs are mediated through two receptor subtypes: CRF receptor 1 (CRFR1) and CRFR2. Their physiological roles, among other functions, include the regulation of food intake and anxiety-like behavior. In this review, we describe the progress that has been made towards understanding how anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…Consistent with previous literature, a decrease in food intake was also observed following UCN2 dosing (Fig. 2J) (Nakayama et al, 2011;Ohata & Shibasaki, 2004).…”
Section: Acute Ucn2 Treatment Induces Insulin Resistancesupporting
confidence: 92%
“…Consistent with previous literature, a decrease in food intake was also observed following UCN2 dosing (Fig. 2J) (Nakayama et al, 2011;Ohata & Shibasaki, 2004).…”
Section: Acute Ucn2 Treatment Induces Insulin Resistancesupporting
confidence: 92%
“…Peripheral administration of VacA increased the number of c-Fos-positive cells in the PVN of the hypothalamus; these cells were also positive for Ucn1, indicating that VacA activated Ucn1-positive neurons in the PVN. Ucn1 is a 40-amino-acid peptide belonging to the CRF peptide family that exerts anorexigenic and anxiogenic effects 34 . Previous studies reported the distribution of Ucn1 in the brain including hypothalamus, Edinger–Westphal nucleus 35 , and the median eminence 36 and the strain dependency in mice 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, after 2 more hours, NPB caused appetite suppression. The same study evaluated the effects on appetite of co-administration of NPB and corticotropin-releasing factor (CRF), a well-known suppressor of food intake [ 29 ]. Tanaka et al reported that CRF significantly enhanced the suppression of appetite induced by NPB, suggesting an interaction between CRF and urocortin systems [ 11 ].…”
Section: The Role Of Npb In Appetite Modulationmentioning
confidence: 99%